Using behavioral change as a tool to reduce healthcare associated infections in a low resource setting - Jaggi, Namita; Sissodia, Pushpa (International Journal of Infection Control, 2014)
Infection Prevention is an old science but a new art. The reasons for non-compliance to infection control practices in healthcare settings are related to psychological barriers, preconceived notions, cultural influences and ineffective time and resource management. Can we use behavioral change as a powerful tool to improve infection control practices and reduce healthcare associated infections (HAI)? This study was carried out for one year from July 2012 to June 2013. 24 infection preventionists were identified. A baseline assessment of their awareness and compliance in infection prevention was undertaken followed by understanding the psychological blocks by a trained psychologist who then addressed the issues. A post training assessment was conducted and results statistically analyzed. Results showed that 19 of the 24 (79%) showed significant improvement (p<0.05) in all aspects of competency in infection prevention. A positive correlation was observed between the compliance to infection control practices and decrease in HAI. In conclusion, understanding human behavior leading to low compliance to infection control practices and imparting training to overcome these blocks can be a powerful, cost effective and a rational approach to reduce HAI in low resource settings.